CVEMP and VAT for the diagnosis of vestibular migraine. (2nd August 2021) - Yao, Yufang; Zhao, Zhiyue; Qi, Xiaoyuan; Jia, Hongning; Zhang, Lihua
Abstract: Background: Although the diagnostic criteria of vestibular migraine (VM) have already been defined, various clinical manifestations of VM and the lack of pathognomonic biomarker result in high rate of misdiagnosis and mismanagement. A timely and accurate diagnosis tool for the evaluation of VM is highly needed. Objective: The current study aims to investigate the potential feasibility of cervical vestibular evoked myogenic potential (cVEMP) and vestibular autorotation test (VAT) as a diagnosis tool for VM. Methods: A total of 211 subjects were recruited into the current study with all subjects meeting the inclusion and exclusion criteria. The subjects were divided into 3 groups: healthy control group, general migraine group and VM group. Test of cVEMP and VAT was conducted in all the groups, and the generated data were statistically compared. Results: Compared with the other two groups, cVEMP P13‐N23 amplitudes of VM patients showed a significant decline. Mean latency values of the VM group had no significant difference in comparison with other groups. Asymmetry ratios showed increased level in VM patients compared to the control groups, without significant difference. VAT results showed that all the horizontal gain, horizontal phase, vertical gain and vertical phase differ from the other two groups to varying degrees at higher frequency. Conclusion: cVEMP and VAT have potential usage in the assessment of VM and can serve as powerful tool in diagnosis of VM.